Co-delivery of doxorubicin and the traditional Chinese medicine quercetin using biotin–PEG2000–DSPE modified liposomes for the treatment of multidrug resistant breast cancer. Issue 114 (1st December 2016) - Zhang, Jiulong; Luo, Yue; Zhao, Xiufeng; Li, Xiaowei; Li, Kexin; Chen, Dawei; Qiao, Mingxi; Hu, Haiyang; Zhao, Xiuli
Abstract : At present, multidrug resistance (MDR) in cancer therapy is an international problem, which is caused mostly by the overexpressed P-glycoprotein (P-gp) efflux pump. Abstract : At present, multidrug resistance (MDR) in cancer therapy is an international problem, which is caused mostly by the overexpressed P-glycoprotein (P-gp) efflux pump. To address this issue and effectively deliver chemotherapeutic drugs to cancer cells, a liposomal drug delivery system (DOX/QUE BPL) has been designed for the co-delivery of the antitumor drug doxorubicin (DOX) and the traditional Chinese medicine quercetin (QUE). The MTT assay demonstrated that DOX/QUE BPL showed the highest cytotoxicity of all formulations tested against MCF-7/adr cell lines due to the inhibition of P-gp caused by QUE. The same result could also be confirmed by cellular uptake assay. To investigate the mechanism by which QUE reverses the MDR effect, DOX accumulation and efflux, P-gp expression and ATP content determination were measured and the results indicated that QUE could downregulate the expression of P-gp and facilitate drug accumulation in the cytoplasm, thereby reversing the MDR effect. In vivo antitumor activity studies demonstrated that DOX/QUE BPL could reach higher antitumor activity than other reference preparations for MCF-7/adr solid tumors. Histological assays indicated that this preparation could decrease the cardio toxicity arising from DOX and induce apoptosis in solid tumors. Meanwhile, this preparation could also downregulate the expression of P-gp in vivo . All this evidence demonstrated that this liposomal formulation is a suitable carrier for co-delivery of chemotherapeutic drugs to overcome MDR.